DAO ĐỘNG TỰ CHẤN CỦA BẢN MỎNG CHỮ NHẬT TRÊN NỀN ĐÀN HỒI HAI HỆ SỐ NỀN - Đa, Hoàng Văn; Sơn, Trần Đình (Vietnam Journal of Science and Technology, 2012)
SELF - EXCITED OSCILLATION OF THE RECTANGULAR THIN PLATE ON THE ELASTIC FLOOR WITH TWO COEFFICIENTS OF THE FLOOR In this paper, the author has used the asymptotic method to study the seft - excited oscillation of the rectangular thin plate on the elastic floor with two ceoffcients of the floor. The model of the calculation for finding the asymptotic solution of the proplem has been construeted. In the improved first approximation the partial solution of equation of the considered boundary value proplem is determined, further the stability condition of the stationary oscillation has been investigated. The partial frequence of the observed system has increased. The amplitude of the stationary oscillation has been decreased. Thus the proplem was changed on the peculiarity. It is an unexpected new result, which we have obtained.